Non - English Mayor Students’ Attitudes Toward English Lesson at Batanghari University - Yanti Ismiyati; Ridho Praja Dinata (Jurnal Ilmiah Dikdaya, 2020)
This research is aimed at analyzing the attitude of students of non-English major study towards English lessons at the faculty of Economics and Law of Batanghari University in Jambi. The research problem is the attitude of students of non-English major study towards English lessons. The research is used quantitative method by using questionnaire and discussion method. Based on the calculation of the item values using SPSS, it was concluded that 40 questions were valid, 5 were invalid, the total score correlation value (r count) was consulted with rtable (0.349) at α = 0.05, 40 questions were declared valid and as many as 5 questions were declared invalid namely question no. 7,18,19 25 28 and the non-valite questionnaire was discarded. So the number of items used as research is as many as 40 questions. Based on table 4.3 above, can be seen an overview of each variable. Variable Attitute Height with an average value of 3.74. This means that Behavioral is in the High category which is in the High category with an average value of 3.88. Cognitive variable 3.97 and emotional included in the high category that is equal to 3.85. Variable of ATTITUDES of 10 statement items there is one item in the very high category (8) the rest, all items are in the high category with an average value in the range, 3.40 - 4.19 overall, Variable of ATTITUDES is in the category high with an average value of 3.86. Variable of BEHAVIORAL Of the 10 statement items there is one item in the very high category (8) the rest, all items are in the high category with the average value in the range, 3.40 - 4, 19 overall, the Variable of Behavioral is in the high category with an average value of 3.88.COGNITIVE out of the 10 statement items there is one item in the very high category (8) and the rest, all items are in the high category with an average value on range, 3.40 - 4.19 overall, QUESTIONAIRES OF COGNITIVES are in the high category with an average value of 3.97. EMOTIONAL OF 10 statement items there is one items are in the very high category (8) the rest, all items are in the high category with an average value in the range, 3.40 - 4.19 overall, QUESTIONAIRES OF EMOTIONAL are in the high category with an average value of 3.85.